Diagnostic accuracy of skin prick test and specific IgE and their association with Total IgE, AEC and serum cortisol in Indian patients with respiratory allergy - PC Kathuria; Manisha Rai; Neelam (Global Journal of Allergy - Peertechz Publications, 2021)
Background: Indian subcontinent has high burden of patients suffering from respiratory allergy associated with food sensitization. Immune response is different in skin and blood for allergen sensitization. Skin Prick Test (SPT) and Specific IgE (s IgE) allergen positivity is an evidence of sensitization. Both these tests (SPT & sIgE) are often used interchangeably in clinical practice of allergic disorders. In our study the concordance relevance of various tests SPT, sIgE, Total IgE, Absolute Eosinophil Count (AEC) & Serum Cortisol was investigated in 75 patients of respiratory allergy. The aeroallergens were divided into four groups (Dust mite, Pollen, Fungi, Cockroach) & 7 Foods (Milk, Soybean, Wheat, Fish, Peanut, Egg white, Yeast). Total 35 common allergens were tested by SPT. Serum Specific IgE estimation was carried out with 16 allergens (D. pteronyssinus, D. farinae, Alternaria alternata, Candida albicans, Aspergillus fumigatus, mesquite (Prosopis juliflora), common pigweed, goosefoot lamb's quarter (Chenopodium album), cockroach and seven food allergens (milk, soybean, wheat, fish, peanut, egg white, yeast). Methods and findings: A retrospective stratified sample of 75 respiratory allergic patients within age group of 05-70 years was included in the study. Serum total IgE and specific IgE levels were estimated by using ImmunoCAP® system and SPT was done by standardized allergens (Allergo Pharma and Greer laboratories Inc.). Following results were compared to evaluate concordance/ discordance between various markers for respiratory allergy. 1. Sensitizations pattern based on Serum (16 specific IgE >1 kU/ml) with Skin prick tests Positive >4 mm wheal Size (35 aero-allergens) 2. Serum Total IgE levels >250 IU/ml with Sensitizations based on Serum (16 specific IgE >1 kU/ml) with Skin Prick Tests Positive >4 mm wheal Size (35 aero-allergens) 3. Absolute Eosinophil Count >200 cells/uL with Sensitizations based on Serum (16 specific IgE >1 kU/ml) with Skin Prick Tests Positive >4 mm wheal Size (35 aero-allergens) 4. Serum cortisol level <10 mcg/dL with Sensitizations based on Serum (16 specific IgE >1 kU/ml) with Skin Prick Test Positive >4 mm wheal Size (35 aero-allergens).